PERUBAHAN KUALITAS AIR DAN HUBUNGANNYA DENGAN PERTUMBUHAN SEMAI Rhizophora mucronata Lamk. BERDASARKAN WAKTU PENGAMATAN YANG BERBEDA PADA SALURAN TAMBAK WANAMINA - Tyagita Andarani; Endah Dwi Hastuti; Rini Budi Hastuti (Jurnal Akademika Biologi, 2016)
System management of mangrove areas, which are associated with fish farming as a solution of damage to mangrove areas which less productive, called wanamina pond system (silvofishery). Rhizophora mucronata is a kind of mangrove which is susceptible to changes in environmental quality, so it can directly affect its growth. This study aims to know the growth rate of R.mucronata, water quality, and the relationship of the two, based on different observation time on channel of wanamina pond. The methods used in this study called Completely Randomized Design, while the data analysis that is used in the form of analysis of variance (ANOVA) and multiple linear regression analysis. The result of the analysis of variance for growth of R. mucronata’s seed in four months showed that a growing number of leaves, branches, the stands, and the rod diameter from different observation time shows no different results. Water quality parameter that shows different results are temperature and salinity. Analysis of the relationship of water quality with growth of R. mucronata from multiple linear regression indicates that turbidity and pH give influence negatively to growth of diameter for R. mucronata.Keywords: Rhizophora mucronata, Seed Growth, Water quality.